MARKETING STRATEGIES IN THE PROCESS OF ENTERING ENTERPRISES INTO FOREIGN MARKETS: FEATURES AND APPROACHES TO IMPLEMENTATION - LARINA, Yaroslava; DICHENKO, Anna; SYDOROV, Maksym (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article considers conceptual approaches to international marketing and marketing strategies that enterprises should implement when entering into foreign markets. The purpose of the article is to determine the content, factors and conditions of the development strategies of international marketing in the activities of enterprises in foreign markets. To realize the goal, the following tasks were set: clarify the content of marketing of foreign economic activity and international marketing; determine the role and features of marketing in foreign markets; describe the main types and tools of marketing strategies while entering foreign markets; to determine the key trends in the development of modern marketing when entering to the markets of other countries. The authors emphasize that a carefully developed marketing strategy has importance for the successful entering to foreign markets. Such a strategy should take into account the current mission, company goals, factors of the marketing environment and risk assessment. The entry of the enterprise to foreign markets is associated with significant threats and risks, therefore it is necessary to develop a sound marketing strategy and appropriate programs for the development of international markets. Conducting in-depth marketing research is a necessary condition for successful entering into international markets. This allows enterprises to find out basic patterns of consumer behavior, features of competition, and build relationships with local communities. Export, joint ventures, strategic alliances, and franchising are traditionally considered strategies for entering a foreign market. The article provides options for the most effective marketing strategies when entering foreign markets, it is emphasized that from several alternative strategies, enterprises should choose those that are more in line with their goals, resources and needs of target consumers. It has been proven that the field of international marketing does not have a universal decision-making model, but enterprises must follow the main stages of strategy formation and implementation, which will help navigate the complexities of entering the international market, providing them with a comprehensive understanding of risks and opportunities. The advantages of international marketing include diversification, increasing the potential level of profitability, economies of scale, and the possibility of forming various options for competitive advantages. The article also identifies barriers to global expansion when entering foreign markets. Approaches to the formation of an effective marketing strategy on foreign markets have been developed, including standardization and adaptation strategies. In particular, it is stated that the marketing strategy of the enterprise in foreign markets should take into account factors of a socio-cultural nature, the specifics of the legal field, therefore its implementation may involve the translation of advertising texts, a change in the design of the product or packaging, as well as the adaptation of advertising campaigns to local requirements and cultural features of a specific countries.
Keywords: entering foreign markets; marketing; international marketing; marketing strategies; globalization; adaptation